2007
DOI: 10.1007/s10508-007-9280-2
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Work in the Public Performances of Male-to-Female Transsexuals

Abstract: Much research has shown that entering the public sphere is emotionally taxing yet key to male-to-female transsexuals' status passage. Yet, little is known about how transsexuals actively manage their emotions during this important transitional phase. Taking a dramaturgical approach to emotions, we explored how some male-to-female transsexuals managed their emotions in ways that helped generate self-confidence and commitment to their paths. Interviewees engaged in three primary forms of emotion work: (1) prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 51 publications
0
32
0
Order By: Relevance
“…Those individuals who undergo gender affirmation and present publicly as the opposite gender may subsequently 'disappear' into the larger categories of men or women. As Schilt and Connell (2007) Adam's apples, and pitch of one's voice can render some individuals more easily "read" as transgender than others (Schrock, Boyd, & Leaf, 2009). Hormones, electrolysis, cosmetics, and surgery can help individuals "pass", but not everyone has financial access to these treatments, nor do they necessarily render individuals indistinguishable from the cisgender population.…”
Section: Assimilationmentioning
confidence: 99%
“…Those individuals who undergo gender affirmation and present publicly as the opposite gender may subsequently 'disappear' into the larger categories of men or women. As Schilt and Connell (2007) Adam's apples, and pitch of one's voice can render some individuals more easily "read" as transgender than others (Schrock, Boyd, & Leaf, 2009). Hormones, electrolysis, cosmetics, and surgery can help individuals "pass", but not everyone has financial access to these treatments, nor do they necessarily render individuals indistinguishable from the cisgender population.…”
Section: Assimilationmentioning
confidence: 99%
“…Similar to how nascent male-to-female transsexuals engage in ''personal pep talks'' to control fear when preparing to go out in public as women (Schrock, Boyd, and Leaf 2009), fighters' masculinist self-talk bolstered their confidence as they set forth to bash symbolic women.…”
Section: Otheringmentioning
confidence: 99%
“…This pilot study further emphasized that smoking was largely a social activity for young LGBT adults and often a response to stressors of LGBT discrimination or limited family support. Other studies have found relationships with LGBT smoking and gender atypicality (Schrock, Boyd, & Leaf, 2009), stress related to stigmatization and internalized homophobia (T. L. Hughes & Jacobson, 2003), sensation seeking (Trocki, Drabble, & Midanik, 2009), early sexual debut (Lombardi, Silvestre, Janosky, Fisher, & Rinaldo, 2008), and greater bar participation (Rosario, 2008). Although these studies are important in suggesting potential contributors to LGBT smoking and areas requiring attention for counselors providing services to LGBT smokers, we know very little as to differences between LGBT occasional smokers and those who become heavy smokers or are nicotine dependent.…”
Section: Introductionmentioning
confidence: 87%